Ghost to the rescue - Hart, Carolyn G. (Hart, Carolyn G. Bailey Ruth ghost mysteries, 2015)
"New York Times bestselling author Carolyn Hart's ghostly gumshoe Bailey Ruth Raeburn is frequently amusing...but this is the first time she's been a muse. When you wish upon a star, you get...Bailey Ruth? You do if you're a little girl whose mom needs help and you touch the soft heart of Supervisor Wiggins at Heaven's Department of Good Intentions. Granted it's not the usual task of an emissary, but then again Bailey Ruth is not your usual emissary. So Wiggins dispatches the spunky spirit to her old hometown of Adelaide, Oklahoma, to help a single mother and struggling writer find some creative solutions to her problems. Deidre Davenport is just about broke, trying to support her two children, and has her hopes pinned on getting a faculty job with the Goddard College English department. Jay Knox, who is in charge of the writer's conference she's participating in, will decide who gets the job, but he's more interested in her body than her body of work. Not long after his advances are rejected, Knox turns up dead--and Deirdre's fingerprints are found on the murder weapon. Bailey Ruth knows Deirdre is innocent, and that the professor's lewd behavior is bound to have rubbed others the wrong way. Now she must find out who really knocked off Knox...if Deirdre and her family are ever going to have a happy ending"--